Using Strategic Cost Management Techniques for Reducing Banking Risks: Applied Study - Azhar Ghailan Marhoon Al-Zubaidi; Hesham Khalif (Harmoni Economics: International Journal of Economics and Accounting, 2025)
In alongside demonstrating how strategic cost management approaches can lower banking risks, the study sought to address the theoretical underpinnings of both banking risks and strategic cost management techniques. as well as identifying the most important measures through which banking risks to which economic units are exposed can be reduced to a minimum by helping to deal with situations in which the future cannot be predicted with certainty and that banking risks arise from the financing side. The study was applied in a sample of banks listed on the Iraq Stock Exchange, and the focus was on commercial banks because of the exposure of these banks to a range of banking risks, the most important of which are credit risks, liquidity, exchange rate and interest rate. These banks also suffer from problems related to operational decisions such as pricing decisions. Strategic cost management techniques are a set of tools and methods that are appropriate to the needs of the modern business environment, which is concerned with cost analysis in a broad framework through its ideal position in order to improve the cost structure and achieve competitive advantage. This was the most significant finding of the research. The research discovered that strategic cost management techniques can help reduce risks and rationalize operational decisions, through which they can respond quickly to customer requirements and provide sufficient flexibility for any Changes that may occur and the delivery of products to them as quickly as possible while adhering to the standards of the modern corporate environment.